2004
DOI: 10.1007/s10350-004-0561-8
|View full text |Cite
|
Sign up to set email alerts
|

Cap Polyposis: Further Experience and Review

Abstract: Cap polyposis is eminently treatable with good long-term prognosis and function. Patients with solitary cap polyp respond well to endoscopic polypectomy. However, patients with multiple polyps and concurrent anorectal pathology require surgical resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 18 publications
0
41
0
Order By: Relevance
“…Cap polyposis in humans is a rare disease characterized by the presence of polyps covered by a "cap" of granulation tissue [4,22,31]. Endoscopically, these polyps occur in multiples (1-100 polyps), and are small, reddish, and sessile.…”
Section: Discussionmentioning
confidence: 99%
“…Cap polyposis in humans is a rare disease characterized by the presence of polyps covered by a "cap" of granulation tissue [4,22,31]. Endoscopically, these polyps occur in multiples (1-100 polyps), and are small, reddish, and sessile.…”
Section: Discussionmentioning
confidence: 99%
“…The avoidance of excessive straining during defecation has been reported as a successful treatment strategy in some cases (12). On the other hand, some authors reported that chronic straining or constipation was noted in only 7 out of the 11 patients (64%) (13). Also, the infant in our case report showed normal results in the anorectal motility study, no constipation, and no evidence of abnormal motility of the colon.…”
Section: Discussionmentioning
confidence: 99%
“…The author suggested that helper T-cell mediated inflammation is the mechanism for explaining the pharmacodynamic effectiveness of steroids or infliximab (14). However, there are many reports on the failure of steroids or infliximab (1315). Consequently, it is controversial whether steroids or infliximab should be administered uniformly.…”
Section: Discussionmentioning
confidence: 99%
“…The common presentations are rectal bleeding, mucous diarrhea, or tenesmus. The number of polyps can vary from 1 to over 100 [32]. They are sessile or semipedunculated.…”
Section: Inflammatory Polyposismentioning
confidence: 99%